If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 7 = 10 Reorder the terms: 7 + N = 10 Solving 7 + N = 10 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + N = 10 + -7 Combine like terms: 7 + -7 = 0 0 + N = 10 + -7 N = 10 + -7 Combine like terms: 10 + -7 = 3 N = 3 Simplifying N = 3
| 2c+4-3c=2n+12 | | .7m+.7=.7 | | 14=l+7 | | 9c+6=-30 | | 5h-7=2h+8 | | 3x^2+4x-12=120 | | x+52=-12 | | 8w-17=12w+7 | | 9K+4=-14 | | 6x+5-2x=8x+21 | | -(8z+2z-1)= | | -24=6a-15-5x | | 4+y=12 | | -0.5x^2+x+3.5=0 | | -8j-1=1 | | 13q+91-13q= | | 8x^2-15x=0 | | -18=14y+10 | | x^4-12x^2+27=0 | | 3.65+e=24.81 | | 8(3x-4)=(9x+3)+7 | | Z-17.2=-47.62 | | 0.03x-0.6=0.75 | | 5.7=9+p | | .7x=1.05 | | 4x*2+11x+6=0 | | 3-2(y-1)=2+4y | | 4x-34=7x+x-14 | | x+(x+6)=54 | | -6b+7+4b=-3b+12 | | x(x+6)=54 | | 2(4)-3(-4)+1=4+25 |